AVOCADO MARKETING EFFICIENCY IN RANUYOSO VILLAGE, LUMAJANG DISTRICT - Hikmatul Lutfi`ah; Amanah Lailatul Ikrimah (AGRIBEST, 2019)
Avocados are fruits rich in benefits and produce as many as 78.067 tons during 2017 in East Java. Ranuyoso village, Lumajang District is one of the areas were producing of avocado in East Java. This study aims to analyze the marketing of avocados in Ranuyoso Village, Ranuyoso District, Lumajang Regency, and examine the efficiency of marketing. The method used in this study is a descriptive analysis of marketing channels, farmer shares and the efficiency of marketing avocados. The result showed that were three avocado marketing channel, all of its efficiency value below 30% and the most efficient channel was channel III with the smallest marketing cost. Largest farmer shares showed in channel III.